Nilai-nilai Moderasi dalam Pembelajaran Pendidikan Agama Islam pada Sekolah Menengah Atas - Rahman, Rini; Rambe, Anggi Afrina; Murniyetti, Murniyetti (FONDATIA, 2023)
Religious moderation is the foundation for schools to respect differences so that tolerance is instilled in the souls of students to respect one another. This study aims to explore the values contained in religious moderation contained in Islamic religious education learning materials. This study uses a qualitative method with a case study approach that describes and analyzes the inculcation of religious moderation values in students, as well as data collection techniques using purposive sampling. Data was collected through interviews with four informants, observation and documentation, and analyzed using interactive analysis using the Milles & Huberman model. From the results of this study, there are five values of religious moderation, namely: (1) Al-I'tidal (Perpendicularity and being proportional), (2) At-Tasamuh (Tolerant), (3) Asy-Syura (Deliberation), ( 4) Al-Muwathanah (Love of the motherland), and (5) I'tiraf al-'Urf (Cultural Friendly. Related to this, it can be used as a guideline to be developed in education with a broad scope.